2013
DOI: 10.1590/0102-311x00134812
|View full text |Cite
|
Sign up to set email alerts
|

Doenças crônicas e qualidade de vida na atenção primária à saúde

Abstract: The aim of this cross-sectional study was to evaluate quality of life in chronic patients treated at primary care services associated with the Catholic University of Pelotas, Rio Grande do Sul State, Brazil. Quality of life was assessed by WHOQOL-Bref, and data on chronic diseases were obtained from patients' medical records and categorized as cardiovascular diseases, respiratory diseases, endocrine diseases, mental illness, and other musculoskeletal diseases. A total of 920 subjects were interviewed. Low self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 29 publications
6
24
0
17
Order By: Relevance
“…The association between a greater number of morbidities and low scores in the physical domains of HRQOL can be related to pain, discomfort, dependency on medication use and need to treat the disease in health services [33][34][35] . These domains have been more sensitive to the impact of chronic disease in other studies using the SF-36, and deserve special attention in the evaluation of individuals, especially with advancing of age 36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between a greater number of morbidities and low scores in the physical domains of HRQOL can be related to pain, discomfort, dependency on medication use and need to treat the disease in health services [33][34][35] . These domains have been more sensitive to the impact of chronic disease in other studies using the SF-36, and deserve special attention in the evaluation of individuals, especially with advancing of age 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that there was an internal validity through an appropriate methodology to calculate the sample size taking into account the variation of the scores obtained in the pilot study, in addition to the selection of households with probability proportional to the size of PSUs, method suitable for population surveys 33 . The use of structured methods for data collection and interpretation of data contributed to the internal validity of our conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This instrument allows describing the subjective perception of individuals in relation to their physical and psychological health, social relationships and the environment in which they live 8 . It is observed that several studies performed in Brazil evaluated the QOL of individuals in specific populations, such as the elderly and pregnant women, [9][10][11] or in those with different health problems [12][13][14] . On the other hand, few studies have evaluated the QOL of the general population, with different health profiles, such as those attended by the Primary Health Care (PHC) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…PHC is patients' gateway to the Unified Health System (SUS), with a capacity to respond to 85% of health needs and problems of the general population, with preventive, curative and health promotion services, as well as integrate care and address the life context of individuals 16 . Studies performed in the context of primary care observed a variability of QOL perception, pointing to the domain "social relationships" as the one with the greatest contribution to a good QOL, and the "environment" domain with the lowest contribution 9,11,12,15,17 . Diseases, low adherence to treatment and low educational level are factors associated with poorer perception of QOL in individuals serviced at PHC facilities 18,19 .…”
Section: Introductionmentioning
confidence: 99%